Saturated Magnetization in Sm and Tb Doped La(Fe0.88Si0.12)13 - Hiep, Vuong Van; Thi Kim Anh, Do; An Bang, Ngac; Nam Nhat, Hoang; Dang Chinh, Huynh (VNU Journal of Science: Mathematics - Physics, 2019)
Abstract : The saturated magnetization in 20% substituted La 0.8 R 0.2 (Fe 0.88 Si 0.12 ) 13 (R = Sm, Tb) magneto-caloric alloys is discussed in this work.  The measurements were taken up to 70 kOe (7 Tesla) to detect the saturation of magnetic moments. As reported recently [Mat. Trans. 59(7) (2018) 1068], these compounds show a large variation of magnetic entropies at low field variation (~ 1.5 T), which associate with the large relative cooling efficiency (RCP) of 52 (for Tb-doped) and 102 J/kg (for Sm-doped) even at low effective D H of ~ 15 kOe. We re-detected the effective range of field variation D H and recognized that the effective D H ~ 5 kOe which is much lower than the value of other magneto-caloric compounds and is excellent for application of Sm-doped compound in modern cooling devices. Keywords: Magnetic, alloys, LaFe 13 , phase transition, rare-earth. References [1] V.K. Pecharsky, K.A. Gschneidner, Tunable magnetic regenerator alloys with a giant magnetocaloric effect for magnetic refrigeration from ∼20 to ∼290 K, Appl. Phys. Lett. 70 (1997) 3299. https://doi.org/10.1063/1.119206 [2] T.T.M. Palstra, G.J. Nieuwenhuys, J.A. Mydosh and K. H. Buschow, Mictomagnetic, ferromagnetic, and antiferromagnetic transitions in La(FexAl1−x)13 intermetallic compounds, J. Phys. Rev. B 31 (1985) 4622. https://doi.org/10.1103/PhysRevB.31.4622 [3] O. Tegus, E. Bruck, K. H. J. Buschow, and F. R. de Boer, Transition-metal-based magnetic refrigerants for room-temperature applications, Nature (London) 415 (2002) 150. https:// doi.org/10.1038/415150a [4] J. Marcos, A. Planes, L. Mañosa, F. Casanova, X. Batlle, A. Labarta, and B. Martínez, Magnetic field induced entropy change and magnetoelasticity in Ni-Mn-Ga alloys, Phys. Rev. B 66 (2002) 224413. https://doi.org/10.1103/PhysRevB.66.224413 [5] Vuong Van Hiep, Nguyen Khac Thuan, Do Thi Kim Anh, and Hoang Nam Nhat, Crystal Structure and Magnetic Properties of La0.8R0.2(Fe0.88Si0.12)13 (R = Sm and Tb) Compounds, Mat. Trans. 59(7) (2018) 1068. https://doi.org/10.2320/matertrans.MD201716 [6] Z.B. Guo, Y.W. Du, J.S. Zhu, H. Huang, W.P. Ding, D. Feng, Large Magnetic Entropy Change in Perovskite-Type Manganese Oxides, Phys. Rev. Lett. 78 (1997) 1142. https://doi.org/10.1103/PhysRevLett.78.1142 [7] T.T.M. Palstra, J.A. Mydosh, G.J. Nieuwenhuys, A.M. Van der Kraan, K. H. Buschow, Study of the critical behaviour of the magnetization and electrical resistivity in cubic La(Fe, Si)13 compounds, J. Magn. Magn. Mater. 36 (1983) 290. https://doi.org/10.1016/0304-8853(83)90128-2 [8] Van Hiep Vuong, Kim Anh Do Thi, Khac Thuan Nguyen, Van Hong Le, and Nam Nhat Hoang, Magnetocaloric effect and the influence of pressure on magnetic properties of La-excess pseudo-binary alloys La1+δ(Fe0.85Si0.15)13, J. Appl. Phys. 120 (2016) 142120. https://doi.org/10.1063/1.4961715 [9] A. Fujita, Y. Akamatsu, and K. Fukamichi, Influence of pressure on itinerant electron metamagnetic transition in La(FexSi1−x)13 compounds, J. Appl. Phys. 85 (1999) 4756. https://doi.org/10.1063/1.1556246 [10] S. Fujieda, A. Fujita, K. Fukamichi, Reduction of hysteresis loss in itinerant-electron metamagnetic transition by partial substitution of Pr for La in La(FexSi1−x)13, J. Magn. Magn. Mater. 310 (2007) e1004. https://doi.org/10.1016/j.jmmm.2006.10.960 [11] D.T.K. Anh, N.P. Thuy, N.H. Duc, T.T. Nhien, N.V. Nong, Magnetism and magnetocaloric effect in La1−yNdy(Fe0.88Si0.12)13 compounds, J. Magn. Magn. Mater. 262 (2003) 427. https://doi.org/10.1016/S0304-8853(03)00073-8 [12] P. Kumar, N.K. Singh, K.G. Suresh, A.K. Nigam, Structural, magnetic and magnetocaloric properties of La0.8Gd0.2Fe11.4Si1.6, Physica B 403 (2008) 1015. https://doi.org/10.1016/j.physb.2007.10.289 [13] Do Thi Kim Anh, Vuong Van Hiep. Samples preparation, structure and magnetic properties of La(Fe¬1-xSix)13 compounds, VNU J. Sci: Math. Phys. 28(1S) (2012) 1. [14] Do Thi Kim Anh, Vuong Van Hiep, Makio Kurisu, Dinh Van Chau, Hoang Nam Nhat, Effect of Cerium Doping on Crystal Structure and Magnetic Properties of La1−yCeyFe11.44Si1.56 Compounds, Mat. Trans. 56(9) (2015) 1335. https://doi.org/10.2320/matertrans.MA201518